The effect of temperature on the tribological properties of palm kernel activated carbonepoxy composite - Mat Tahir, Noor Ayuma; Abdollah, Mohd Fadzli bin; Hasan, Rafidah; Amiruddin, Hilmi (jstage, 2015)
The aim of this study was to investigate the effect of temperature on the tribological properties of Palm Kernel Activated Carbon-Epoxy (PKAC-E) composite. All specimens were formed into 10mm diameter pins of 30mm length, using a hot compaction technique. Tribological testing was carried out using a pin-on-disc tribometer in dry sliding conditions by applying temperatures in the range of 27oC to 150oC, at constant sliding speed, applied load, and sliding distance. The results showed that both coefficients of friction (COF) and wear rate of the composite increased with operating temperatures. Abrasive wear and crack formation that would induce delamination wear were identified as the predominant wear mechanisms.